PENGARUH DETERMINAN PERDAGANGAN BILAT- ERAL INDONESIA-AUSTRALIA TERHADAP TOTAL EKSPOR INDONESIA DENGAN PENDEKATAN GRAVITY MODEL - Efendi, Reyne Niang; Munawar (Contemporary Studies in Economic, Finance and Banking, 2022)
The economic cooperation between Indonesia and Australia has existed for a long time, including in terms of export and import, one of which is contained in the IA-CEPA agreement. However, the trend of growth in Indonesia's imports to Australia tends to be more stable in value than its exports. Geographical proximity is also important for the two countries to support each other's economy, especially in terms of trade, so this study uses a gravity model approach. The purpose of this study was to determine the effect of the distance from the exporting country (Indonesia) to the destination country (Australia), Australia's GDP, Australian population, real exchange rate, and the economic crisis on Indonesia's total exports. This study is a quantitative study using secondary time series data in the form of annual data for the period 1991 to 2020. In this study, the authors used E-views 9 software for processing the collected data.